Methodology for assessing the food environment as part of research on food systems for healthier diets - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Initially compiled for stakeholders participating in A4NH workshops in 2019. In 2020, A4NH researchers incorporated these methods in three contexts; results not yet publicly available. Other pilots started from 2020 onwards with World Food Program's fresh food voucher program and in six countries participating in Horizon 2020’s “food systems labs”